2019
DOI: 10.1002/pra2.39
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and representation of intangible cultural heritage knowledge using linked data and ontology

Abstract: Intangible cultural heritage (ICH) contains rich knowledge, and the effective organization and management of ICH knowledge is the foundation for the protection and inheritance of ICH. The development of semantic Web technology changes the way of knowledge representation and expression and provides new ideas and methods for the organizing and sharing of ICH knowledge. This paper describes a research project: to model and manage the ICH knowledge by publishing the knowledge as linked data. Firstly, a knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…This calls for knowledge of how to capture, preserve, migrate and conserve video, audio, photo documentation, and text. Metadata standards for art may need to be expanded to meet these definitions (Harpring, 2010; Hou and Wang, 2019; Ziku, 2020), and to enable linking and discovery.…”
Section: Literature Review and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This calls for knowledge of how to capture, preserve, migrate and conserve video, audio, photo documentation, and text. Metadata standards for art may need to be expanded to meet these definitions (Harpring, 2010; Hou and Wang, 2019; Ziku, 2020), and to enable linking and discovery.…”
Section: Literature Review and Methodologymentioning
confidence: 99%
“…Hou and Wang (2019) explore knowledge ontology to support “abundant knowledge” and “internal relationships” of linked, interoperable and open intangible cultural heritage data. Houxilong (2019) notes top level categories including “inheritors” of knowledge, “categories,” and “place,” and expands to properties such as mentors and individuals who have influenced practitioners.…”
Section: Literature Review and Methodologymentioning
confidence: 99%
“…Then, an intangible heritage knowledge network was created based on the intangible cultural heritage projects of Hubei and Hunan provinces. Hou et al (2019) also focused on the elements and semantic relations of intangible cultural heritage knowledge and designed an ontology model of intangible cultural heritage knowledge. The authors paid more attention to the publication and dissemination of knowledge and selected Hubei Province as an example to build the linked dataset and knowledge service platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This process requires an adequate understanding and analysis of digital resources when defining classes. Previous studies have also shown that researchers often reuse domain ontologies, typically including CIDOC-CRM to describe cultural heritage and FOAF to describe people (Krabina, 2023;Hou et al, 2019). The domain ontology, which describes a set of representational primitives to model domain knowledge, provides a common and unequivocal understanding of a domain for users and the system to communicate (Zhou, 2007).…”
Section: Class Definitionsmentioning
confidence: 99%
See 1 more Smart Citation